2021
DOI: 10.3389/fpubh.2021.637351
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Care Delivery for Children During COVID-19 Pandemic—A Retrospective Study

Abstract: Aim: COVID-19 outbreak and the lockdown period following was a very challenging time for pediatric dentistry. We aimed to find whether the characteristics of dental care provided to children at the Department of Pediatric Dentistry at Hadassah medical center, Jerusalem, Israel, differed between the periods, before COVID-19 outbreak, during the lockdown period and during the period that followed it.Materials and Methods: We retrospectively reviewed computerized records of patients who visited the pediatric dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 14 publications
(20 reference statements)
8
28
0
1
Order By: Relevance
“…During the lockdown, the purposes of pediatric patients’ visits in the clinic due to trauma, infection, and treatment continuation were reduced ( Table 2 ). Similar to the studies by Üstün et al [ 29 ] and Fux-Noy et al [ 35 ], herein, the patients’ visits due to pain were higher during the lockdown. Another study reported many trauma cases in males and acute pericoronitis and acute gingivitis cases in females during the lockdown [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…During the lockdown, the purposes of pediatric patients’ visits in the clinic due to trauma, infection, and treatment continuation were reduced ( Table 2 ). Similar to the studies by Üstün et al [ 29 ] and Fux-Noy et al [ 35 ], herein, the patients’ visits due to pain were higher during the lockdown. Another study reported many trauma cases in males and acute pericoronitis and acute gingivitis cases in females during the lockdown [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, in China [ 37 ] and Turkey [ 29 ], a 38% reduction in pediatric dental emergency cases was reported. Other studies in Israel also reported a decrease in dental emergency cases [ 35 , 38 ]. A total of 20.8% of dental emergency cases were treated in South India [ 36 ].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Several studies confirm that during the pandemic dental extractions were performed most frequently. 18 We attribute the decline in the utilization of maxillofacial services in our facility to several reasons: Firstly, the hard lockdown severely restricted the movement of people including visits to healthcare facilities. Secondly, during this period of total shutdown, the world was overwhelmed by anxiety and fear of the virus.…”
Section: Discussionmentioning
confidence: 99%